OPPOSITION "NATIVE - STRANGER" IN FOLK CULTURE (CHILDREN AND ELDERS IN POLISH FOLK CULTURE) - Kalniuk, Tomasz (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In Poland, regardless of the partition or ethnographic region, as well as in other rural cultures in the world, we can observe attitudes towards children and elders whose ambivalent character is typical of mythical paradigm. The youngest and the oldest members of rural societies were usually faced with antipathy or even aggression, as a result of negative attitudes towards their age and consequently, their social status. The former ware immature - the latter were too feeble to be involved in life in society. Moreover, they had to be looked after and supported materially. Thus, they were placed on the borderline between live and death, and between the natural and the supernatural. They were perceived not only as members of society but also as mythical characters - intermediaries with the area of sacrum.